Impacts of permafrost changes on alpine ecosystem in Qinghai-Tibet Plateau - Wang Genxu; Li Yuanshou; Wu Qingbai; Wang Yibo (Science in China Series D: Earth Sciences, 2006)
Alpine cold ecosystem with permafrost environment is quite sensitive to climatic changes and the changes in permafrost can significantly affect the alpine ecosystem. The vegetation coverage, grassland biomass and soil nutrient and texture are selected to indicate the regime of alpine cold ecosystems in the Qinghai-Tibet Plateau. The interactions between alpine ecosystem and permafrost were investigated with the depth of active layer, permafrost thickness and mean annual ground temperature (MAGTs). Based on the statistics model of GPTR for MAGTs and annual air temperatures, an analysis method was developed to analyze the impacts of permafrost changes on the alpine ecosystems. Under the climate change and human engineering activities, the permafrost change and its impacts on alpine ecosystems in the permafrost region between the Kunlun Mountains and the Tanggula Range of Qinghai-Tibet Plateau are studied in this paper. The results showed that the permafrost changes have a different influence on different alpine ecosystems. With the increase in the thickness of active layer, the vegetation cover and biomass of the alpine cold meadow exhibit a significant conic reduction, the soil organic matter content of the alpine cold meadow ecosystem shows an exponential decrease, and the surface soil materials become coarse and gravelly. The alpine cold steppe ecosystem, however, seems to have a relatively weak relation to the permafrost environment. Those relationships resulted in the fact that the distribution area of alpine cold meadow decreased by 7.98% and alpine cold swamp decreased by 28.11% under the permafrost environment degradation during recent 15 years. In the future 50 years the alpine cold meadow ecosystems in different geomorphologic units may have different responses to the changes of the permafrost under different climate warming conditions, among them the alpine cold meadow and swamp ecosystem located in the low mountain and plateau area will have a relatively serious degradation. Furthermore, from the ...